(3t^2+3t-6)(4t^2+4t-24)
===============================
(2t^2-2t-4)(3t^2+6t-9)
3(t^2+t-2)(4)(t^2+t-6)
==============================
2(t-2)(t+1)(3)(t+3)(t-1)
3(t+2)(t-1)(4)(t+3)(t-2)
==============================
2(t-2)(t+1)(3)(t+3)(t-1)
(2) (t+2) / (t+1)
2
Simplify. State the nonpermissible values.
(3t^2+3t-6/2t^2-2t-4)(4t^2+4t-24/3t^2+6t-9)
This is the way I tried solving this:
3t(t-1)6(t-1)/2t(t-1)4(t-1)*4t(t-2)12(t-2)/3t(t+1)9(t-1)
(3)(t)(t-1)(2)(3)(t-1)/(2)(t)(t-1)(2)(2)(t-1)*(2)(2)(t)(t-2)(2)(2)(3)(t-2)/(3)(t)(t-1)(3)(3)(t-1)
After cancelling out all the terms I am left with:
(2)(t-2)(t-2)/(t-1)(t-1)
^ I cant cancel anything off now. But the answer is supposed to be :
2(t+2)/t+1
^ How do I get that answer?
4 answers
Thank you so much Damon :)
You are welcome.
By the way that is undefined if t = -1 so I suppose that might be what is meant by "non-permissible"
By the way that is undefined if t = -1 so I suppose that might be what is meant by "non-permissible"
Thank you and yeah nonpermissible is another word for restrictions.